Education and Skills for Inclusive Growth, Green Jobs and the Greening of Economies in Asia: Case Study Summaries of India, Indonesia, Sri Lanka and Viet Nam - Maclean, Rupert (Technical and Vocational Education and Training: Issues, Concerns and Prospects, 2018)
Education for Sustainable Development; Green Growth; Green Jobs; Inclusive Growth; Equity in the Promotion of Economic Growth; Environmental Education; Green Economies